2004
DOI: 10.1103/physreve.69.025103
|View full text |Cite
|
Sign up to set email alerts
|

Structural vulnerability of the North American power grid

Abstract: The magnitude of the August 2003 blackout affecting the United States has put the challenges of energy transmission and distribution into limelight. Despite all the interest and concerted effort, the complexity and interconnectivity of the electric infrastructure have so far precluded us from understanding why certain events happened. In this paper we study the power grid from a network perspective and determine its ability to transfer power between generators and consumers when certain nodes are disrupted. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
880
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,195 publications
(911 citation statements)
references
References 13 publications
18
880
2
11
Order By: Relevance
“…Furthermore, the research [80] suggested that the degree distribution of the power grid seemed to be scale-free following a power law distribution function, although not all of the subsequent works have agreed on this [33]. In this respect, some other works have also found that there are exponential cumulative degree functions, for instance in the Californian power grid [73] and in the whole U.S. power grid [105]. This notwithstanding, on the other hand, reference [106] has shown that the topologies of the North American eastern and western electric grids can be analyzed based on the Barabasi-Albert network model, with good agreement with the values of power system reliability indices previously obtained from standard power engineering methods.…”
Section: Power Grids: Is There a Dominant Topology?mentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the research [80] suggested that the degree distribution of the power grid seemed to be scale-free following a power law distribution function, although not all of the subsequent works have agreed on this [33]. In this respect, some other works have also found that there are exponential cumulative degree functions, for instance in the Californian power grid [73] and in the whole U.S. power grid [105]. This notwithstanding, on the other hand, reference [106] has shown that the topologies of the North American eastern and western electric grids can be analyzed based on the Barabasi-Albert network model, with good agreement with the values of power system reliability indices previously obtained from standard power engineering methods.…”
Section: Power Grids: Is There a Dominant Topology?mentioning
confidence: 93%
“…The review [33] points out that many works [46,86,89,90,105,106,[108][109][110][111][112] have in common that each power grid has been represented using the simplest graph model: undirected and unweighted. This is because these approaches do not include any characterization of the link weights.…”
Section: Unweighted and Weighted Graphs: Which Is The Best?mentioning
confidence: 99%
“…In 2003, the largest power outage took place in North America, which just resulted from a broken-down power plant in Ohio [1]. Traffic paralysis of south China caused by storm in 2008 and Internet congestions [2] are typical examples of cascading failures as well.…”
Section: Introductionmentioning
confidence: 99%
“…many different types of networks have been studied: transportation networks like the railways or airlines networks [1], chemical reaction networks in a cell [2], power grids etc. [3]. A good review of the general theory may be found in [4,5].…”
Section: Introductionmentioning
confidence: 99%